Andrographolide suppresses hypoxia-induced embryonic hyaloid vascular system development through HIF-1a/VEGFR2 signaling pathway - Jin, Zhong; Guo, Qiru; Wang, Zheng; Wu, Xiao; Hu, Wangming; Li, Jiali; Li, Hongfei; Zhu, Song; Zhang, Haidi; Chen, Zixian; Xu, Huan; Shi, Liangqin; et al. (Frontiers in Cardiovascular Medicine, 2023)
Abnormal ocular and development of retinal vasculature may cause postnatal retinopathy. Tremendous progress has been made in the past decade in identifying mechanisms that regulate retina vasculature. However, how to regulate embryonic hyaloid vasculature development is largely unknown. This study aimed to determine whether and how Andrographolide regulates embryonic hyaloid vasculature development. Murine embryonic retinas were used in this study. Whole mount Isolectin B4 (IB4) staining, Hematoxylin and eosin (H&E) staining, Immunohistochemistry (IHC) and immunofluorescence staining (IF) performed to determine whether Andrographolide is critical for embryonic hyaloid vasculature development. BRDU incorporation assay, Boyden chamber migration assay, Spheroid sprouting assay, Matrigel-based tube formation assay performed to evaluate whether Andrographolide regulates proliferation and migration of vascular endothelial cell. Molecular docking simulation and CO-immunoprecipitation assay used to observe protein interaction. Hypoxia condition exists in murine embryonic retinas. Hypoxia induces HIF-1a expression, high expressed HIF-1a interacts with VEGFR2 resulting activating VEGF signaling pathway. Andrographolide suppresses hypoxia induced HIF-1a expression and interrupts the interaction between HIF-1a and VEGFR2 causing inhibiting endothelial proliferation and migration, eventually inhibits embryonic hyaloid vasculature development. Our data demonstrated that Andrographolide plays a critical role in regulating embryonic hyaloid vasculature development.